Inoculation with Azospirillum brasilense associated with silicon applied to correct soil acidity and nitrogen rates in corn and wheat crops - Galindo, Fernando Shintate [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
Alternative management practices are needed to minimize the need for chemical fertilizer use in non-leguminous cropping systems. The use of biological agents which can fix atmospheric nitrogen and promote plant growth has shown potential as an option to improve soil nutrient availability to grass crops. In recent years, studies investigating the effects of silicon (Si) have increased substantially, especially in grain crops. This increased interest in Si is likely due to the beneficial effects of Si application on plant resistance to abiotic and biotic stresses, reflecting on greater plant development. This research was developed to investigate if inoculation of corn and wheat with Azospirillum brasilense associated with Si can enhance nitrogen use efficiency (NUE) and improve plant nutrition and yield, leading to a greater economic profit. The study was set up in a Rhodic Haplustox under no-till system, located in Selvíria, state of Mato Grosso do Sul, Brazil. The field trial took place during the 2015/16 (November-March), 2016 (April-September), 2016/17 (November-March) and 2017 April-September) seasons, with corn and wheat crops in sucession (spring/summer and winter seasons for corn and wheat, respectively). Treatments were tested in a randomized completely block design with four replicates, arranged in a full factorial design 5 × 2 × 2 and included: i) five N application rates, as urea source, applied in side-dressing (0, 50, 100, 150 and 200 kg ha-1); ii) two liming sources (Ca and Mg silicate as Si source and dolomitic limestone); and iii) and two seed inoculation (with and without A. brasilense). Increasing N rates positively influenced corn and wheat nutrition with increased nutrient and Si uptake in shoot, straw and grain, plant development and grain filling, leading to a greater grain yield. The average nutrient uptake in corn straw and grain in descending order was K > N > Ca > Si > Mg > S > P > Fe > Mn > Zn > Cu > B for straw; and N > K > P > S > Mg > Ca > Si > Fe > Zn > Mn > B > Cu for grains. For wheat, the average nutrient uptake was K > N > Si > Ca > S > Mg > P > Fe > Mn > Zn > B > Cu in straw; and N > K > P > S > Mg > Si > Ca > Fe > Mn > Cu > Zn > B in grains. The application of Ca and Mg silicate as a Si source had small effects on corn and wheat development and grain yield. Although silicate application as Si source did not greatly favor NUE, Si also did not negatively affect the inoculation and N fertilization, and correlates positively with nutritional, productive components, soil chemical attributes and corn and wheat grain yield. After four cropping seasons (2015/16, 2016, 2016/17 and 2017, with corn and wheat in succession), silicate application was more efficient as a liming source to reduce soil acidity, with decreased soil H+Al and Al content, and increased pH and base saturation (V). Inoculation with A. brasilense increased NUE in corn crop by 19.1% and wheat by 38.6% (average of both years, in both crops) leading to a greater leaf chlorophyll index (LCI), nutrient uptake, corn development, grain filling, grain yield and operating profit. Also, inoculation could increase corn and wheat leaf N concentration when associated with silicate application. Inoculation provided greater corn grain yield by 5.6% (average of both years). Under high N application rates (200 kg N ha-1), inoculation provided an increase of 11.4% on corn grain yield, in 2015/16. In the absence of N fertilization, inoculation provided an increase of 20.2% in grain yield, in 2016/17. In wheat crop, with application of 200 kg N ha-1, inoculation provided an increase of 22.2% in shoot N uptake, in 2016. Inoculation provided greater wheat grain yield by 6.8% (average of both years). The application of 200 and 140 kg N ha-1 in side-dressing with dolomitic limestone, associated with A. brasilense inoculation provided greater corn grain and wheat yield, respectively. However, the highest economic return was obtained with 100 kg N ha-1, with limestone and inoculation, ensuring profitability from production of irrigated corn and wheat under tropical condition (Brazilian Savannah - Cerrado).

Práticas alternativas de manejo são necessárias para minimizar a necessidade por fertilizantes químicos em sistemas de cultivos com culturas não leguminosas. O uso de agentes biológicos que fixam nitrogênio atmosférico e promovem crescimento de plantas tem demonstrado potencial para aumento na disponibilidade de nutrientes do solo às culturas de gramíneas. Nos últimos anos, estudos investigando os efeitos do silício (Si) têm crescido substancialmente, especialmente em culturas agrícolas de grãos. O crescente interesse no estudo com Si ocorre principalmente em função dos efeitos benéficos de sua aplicação, principalmente em condições de estresse biótico e abiótico, refletindo em maior desenvolvimento das plantas. O objetivo deste estudo foi investigar se a inoculação com Azospirillum brasilense no milho e no trigo associado à aplicação de Si pode aumentar a eficiência de uso do nitrogênio (EUN) e refletir positivamente na nutrição de plantas e produtividade de grãos, propiciando aumento no retorno econômico. O estudo foi desenvolvido em um Latossolo Vermelho distrófico típico em sistema plantio direto, localizado no município de Selvíria, Mato Grosso do Sul. O experimento foi conduzido durante as safras 2015/16 (Novembro-Março), 2016 (Abril-Setembro), 2016/17 (Novembro-Março) e 2017 (Abril-Setembro) com as culturas do milho e trigo em sucessão (milho e trigo cultivados nas estações de primavera/verão e inverno, respectivamente).O delineamento experimental utilizado foi em blocos casualizados, com quatro repetições, disposto em esquema fatorial 5 × 2 × 2, incluindo: i) cinco doses de N em cobertura na forma de ureia (0, 50, 100, 150 e 200 kg ha-1 ); ii) duas fontes de corretivo de acidez do solo (silicato de Ca e Mg como fonte de Si e calcário dolomítico); iii) com e sem inoculação das sementes com A. brasilense. O incremento nas doses de N influenciou positivamente na nutrição do milho e do trigo, com aumento no acúmulo de nutrientes e Si em parte aérea, palhada e grãos, no desenvolvimento das plantas e no enchimento de grãos, propiciando aumento na produtividade de grãos. O acúmulo de nutrientes médio na palhada do milho e nos grãos, em ordem decrescente foi K > N > Ca > Si > Mg > S > P > Fe > Mn > Zn > Cu > B na palhada; e N > K > P > S > Mg > Ca > Si > Fe > Zn > Mn > B > Cu nos grãos. Para o trigo, o acúmulo de nutrientes foi K > N > Si > Ca > S > Mg > P > Fe > Mn > Zn > B > Cu na palhada; e N > K > P > S > Mg > Si > Ca > Fe > Mn > Cu > Zn > B nos grãos. A utilização do silicato de Ca e Mg como fonte de Si pouco influenciou no desenvolvimento e na produtividade do milho e do trigo. Embora o silicato como fonte de Si não tenha influenciado sobremaneira a EUN, o Si não afetou negativamente a inoculação e a adubação nitrogenada, além de correlacionar-se positivamente com as avaliações nutricionais, componentes produtivos, atributos químicos do solo e produtividade de grãos de milho e de trigo. Após quatro safras (2015/16, 2016, 2016/17 e 2017, com milho e trigo em sucessão), a aplicação do silicato de Ca e Mg foi mais eficiente como corretivo de acidez de solo do que o calcário dolomítico, com redução do H+Al e Al e aumento do pH da saturação por bases (V)do solo. A inoculação com A. brasilense aumentou a EUN no milho em 19,1% e no trigo em 38,6% (média das suas safras, para ambas as culturas), propiciando aumento no índice de clorofila foliar (ICF), no acúmulo de nutrientes, no desenvolvimento de plantas, no enchimento de grãos, na produtividade de grãos, com reflexo positivo no lucro operacional do milho e do trigo. Além disso, a inoculação pode aumentar a concentração de N foliar no milho e trigo quando associado à aplicação do silicato. A inoculação propiciou aumento na produtividade de grãos de milho em 5,6% (média das duas safras). Quando associada à dose de N elevada (200 kg N ha-1 ) a inoculação aumentou a produtividade de grãos de milho em 11,4% em 2015/16. Na ausência de adubação com N em cobertura, a inoculação propiciou aumento em 20,2% na produtividade de grãos de milho, em 2016/17. Para a cultura do trigo, com aplicação de 200 kg N ha-1 , a inoculação propiciou aumento de 22,2% no acúmulo de N em parte aérea em 2016. A inoculação propiciou aumento na produtividade de grãos de trigo em 6,8% (média das suas safras). A aplicação de 200 e 140 kg N ha-1 em cobertura, com aplicação de calcário dolomítico e inoculação com A. brasilense propiciou as maiores produtividades de grãos de milho e trigo, respectivamente. Entretanto, o maior retorno econômico foi obtido com a aplicação de 100 kg N ha-1 associado à utilização de calcário dolomítico e inoculação com A. brasilense, garantindo lucratividade na produção de milho e trigo irrigados em região tropical (Cerrado de baixa altitude).
Inoculação com Azospirillum brasilense associado à aplicação de silício para corrigir a acidez do solo e doses de nitrogênio nas culturas do milho e trigo
Keywords: Biological nitrogen fixation on grasses; Economic viability; Nitrogen fertilization with urea; Plant growth promoting bacteria; Silicon use on grasses; Zea mays L.; Triticum aestivum L.; Fixação biológica de nitrogênio em gramíneas; Viabilidade econômica; Adubação nitrogenada com ureia; Bactérias promotoras de crescimento em plantas; Uso de silício em gramíneas